GAMBARAN HISTOPATOLOGIS LIMPA TIKUS PUTIH (Rattus novergicus) JANTAN DIINFEKSI Trypanosoma evansi DAN DIBERI EKSTRAK KULIT BATANG JALOH (Salix tetrasperma Robx) (Histopathological finding of Rat (Rattus novergicus) Spleen Infected with Trypanosoma evansi and Treated with Willow Bark (Salix tetrasperma Roxb) Extract) - Elsa Mariane Ramadani; Hamdani Budiman; Sugito Sugito; Ummu Balqis; Muhammad Hambal; Razali Daud (Jurnal Medika Veterinaria, 2015)
The aim of this research was to determine the histopathological finding of rat (Rattus novergicus) spleen infected with Trypanosoma evansi and treated with willow bark (Salix tetrasperma Roxb) extract.This research used 25 male rats divided into four treatment groups and fed ad libitum. Group 0 (K0) was control group, group I (K1) was infected with 103/0.3 ml. T. evansi, group II (K2), III (K3), and IV (K4) were infected with103/0.3 ml T. evansi and treated with willow bark extract 30, 45, and 60 mg/kg bw, respectively. All groups were treated for 3 consecutive days orally using a stomach tube. On day four, rats were euthanized using chloroform and necropsied, then spleen were collected for histophatological examination. The results showed that all spleen on group K1, K2, K3, and K4 showed hyperplasia of white pulp, hemosiderin, and necrosis with different severity levels compared to normal spleen structure. In conclusion, the administration of willow bark extract at the dose of 30 mg/kg bw has a potency to prevent spleen from T. evansi infection. However, the higher the dose of willow bark extract the higher the level of spleen damage.Key words: spleen, T. evansi, willow bark extract